2011
DOI: 10.1103/physrevb.83.144111
|View full text |Cite
|
Sign up to set email alerts
|

First-principles prediction of phase stability and crystal structures in Li-Zn and Na-Zn mixed-metal borohydrides

Abstract: We use a combination of first principles density functional theory (DFT) calculations and the recently developed Prototype Electrostatic Ground State (PEGS) method to predict low energy crystal structures and study phase stability of Li-Zn and Na-Zn mixed-metal borohydride compounds, i.e., NaZn(BH 4 ) 3 , NaZn 2 (BH 4 ) 5 , LiZn(BH 4 ) 3 and LiZn 2 (BH 4 ) 5 .We find the following: (i) DFT+PEGS successfully predicts low-energy structures in these mixed-metal borohydride systems. (ii) DFT calculations show nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…The combination of two metals is expected to decrease the desorption temperatures compared to the more stable alkali or alkaline earth metal borohydride precursor [3,4]. Similar suggestions were obtained from computational screenings of mixed metal borohydrides based on density functional theory (DFT) [5,6]. In [5], stable mixed borohydrides with promising decomposition temperatures were predicted to have averaged metal electronegativities in the 1.3-1.6 range, and favor M M (BH 4 ) 2−5 combinations with M = Li, Na, K, and M = Zn, Ni, Co.…”
Section: Introductionmentioning
confidence: 62%
“…The combination of two metals is expected to decrease the desorption temperatures compared to the more stable alkali or alkaline earth metal borohydride precursor [3,4]. Similar suggestions were obtained from computational screenings of mixed metal borohydrides based on density functional theory (DFT) [5,6]. In [5], stable mixed borohydrides with promising decomposition temperatures were predicted to have averaged metal electronegativities in the 1.3-1.6 range, and favor M M (BH 4 ) 2−5 combinations with M = Li, Na, K, and M = Zn, Ni, Co.…”
Section: Introductionmentioning
confidence: 62%
“…coarser fast Fourier transform grids) was used to improve the speed of the calculations, requiring a higher energy cutoff than the default to avoid simultaneously reducing the accuracy of the interatomic force calculations. DFT has been successfully applied to a wide variety of solid-state hydrides and hydrogen storage reactions 6,9,[17][18][19][20][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] , however, there are far fewer studies of liquid complex hydrides 21,50 . To study the bulk liquid behavior of the four complex hydrides under a range of thermal conditions, we perform canonical (NVT) Born-Oppenheimer AIMD simulations at 300 K, 500 K and 1000 K. For each compound and temperature, we perform three runs beginning from the solid structure with varied initial velocities to sample a greater portion of phase space (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Compounds with LiZn(BH 4 ) 3 and LiZn 2 (BH 4 ) 5 stoichiometries were proposed by previous theoretical and experimental reports, as described in the introduction 13,14,16,18 . Utilizing DFT, we relax the two experimentally proposed structures (PXD and PND) for LiZn 2 (BH 4 ) 5 (i.e.…”
Section: B Determining Hydrogen Desorption Reactionsmentioning
confidence: 97%
“…Following this work,Černý et al 15 performed a combination of in situ synchrotron powder diffraction and energy minimization (DFT) study on LiZn 2 (BH 4 ) 5 . The authors 15 also proposed a new compound LiZn(BH 4 ) 3 , though LiZn(BH 4 ) 3 is not observed experimentally at ambient pressure and in the temperature range of 100-400 K. Subsequently, motivated by these theoretical and experimental predictions, Aidhy et al performed a phase stability study 16 of Li-Zn mixed-metal borohydride compounds, using a combination of DFT and a recently developed crystal structure prediction method -the prototype electrostatic ground state (PEGS) method 17 . This theoretical DFT+PEGS work successfully predicted a low-energy LiZn(BH 4 ) 3 phase, which has a lower DFT energy than the two-phase mixture of Zn(BH 4 ) 2 and LiZn 2 (BH 4 ) 5 in the previously mentioned PXD structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation